2022
DOI: 10.1523/eneuro.0475-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of the G-Protein-Coupled Estrogen Receptor (GPER) on Rat Embryonic (E18) Hippocampal and Cortical Neurons

Abstract: Estrogen plays fundamental roles in nervous system development and function. Traditional studies examining the effect of estrogen in the brain have focused on the nuclear estrogen receptors (ERs), ERα and ERβ. Studies related to the extranuclear, membrane-bound G proteincoupled estrogen receptor (GPER/GPR30) have revealed a neuroprotective role for GPER in mature neurons. In this study, we investigated the differential effects of GPER activation in primary rat embryonic (E18) hippocampal and cortical neurons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 141 publications
0
11
0
Order By: Relevance
“…However, in previous work, we revealed that classical estrogen receptors do not participate in the development of hippocampal neurons, but that estradiol modifies neuronal morphology by acting on GPER through a mechanism that involves activation of PI3K signaling and expression of Ngn3 ( Ruiz-Palmero et al, 2011 , 2013 ). A later study identified GPER as a neurotrophic promotor for neurite outgrowth of rat E18 hippocampal, but not cortical neurons, indicating that different molecular pathways may account for the neuritogenic effect of estradiol in different brain regions ( Pemberton et al, 2022 ). Similar results are observed with BDNF since it has been shown that during postnatal development BDNF regulates neuronal architecture and spine morphology of neurons within specific brain areas but not others ( Zagrebelsky et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in previous work, we revealed that classical estrogen receptors do not participate in the development of hippocampal neurons, but that estradiol modifies neuronal morphology by acting on GPER through a mechanism that involves activation of PI3K signaling and expression of Ngn3 ( Ruiz-Palmero et al, 2011 , 2013 ). A later study identified GPER as a neurotrophic promotor for neurite outgrowth of rat E18 hippocampal, but not cortical neurons, indicating that different molecular pathways may account for the neuritogenic effect of estradiol in different brain regions ( Pemberton et al, 2022 ). Similar results are observed with BDNF since it has been shown that during postnatal development BDNF regulates neuronal architecture and spine morphology of neurons within specific brain areas but not others ( Zagrebelsky et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The streptavidin–peroxidase method was used for immunohistochemistry analysis of the tissue microarrays. The slides were stained with the GPER1 antibody (PA5-28647; Invitrogen, Carlsbad, CA, USA) [ 12 , 52 , 53 ] and visualized with DAB after incubation with the secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Some mERs present distinct subcellular distributions: mERα is mainly expressed in endolysosomes, mERβ prevails in mitochondria, and the majority of GPER1 is in the plasma membrane (breast cancer cells), endoplasmic reticulum, or Golgi apparatus (hippocampus, cortex, striatum) [ 25 , 26 ]. In particular, mERs are present in cortico-limbic brain areas; e.g., ER-X is mainly localized in the neonatal hippocampus and neocortex, but it was recently also found in the adult brain after ischemic stroke [ 27 ].…”
Section: Interactions With the Cell Membranementioning
confidence: 99%
“…The latest study by Pemberton et al (2022) shed light on the differential effects of GPER1 depending on brain structure. In rat embryonic cerebral tissue, the effects of GPER1 activation by a selective G1 agonist (e.g., neural growth, neural firing activity) were more profound in hippocampal neurons than in cortical neurons, independent of the higher GPER1 expression in the cortex compared to the hippocampus [ 26 ]. The lack of an obvious or inverse correlation between the GPER1 expression level and specific neuroprotective effects suggests that other mechanisms are involved, such as the stimulation of neurogenesis, the inhibition of neuroinflammation, or the modulation of nuclear ER-mediated effects [ 80 , 81 , 82 ].…”
Section: Neuroprotection Mediated By Membrane Ersmentioning
confidence: 99%